STRATEGY OF CUSTOMER SERVICE AS AN IMPORTANT DIRECTION FOR ACHIEVEMENT OF COMPETITIVE ADVANTAGES OF AN INDUSTRIAL ENTERPRISE - Kuziak , V.V.; Motorniuk , U.I.; Stasiuk , N.R. (The actual problems of regional economy development, 2019)
The aim of the article is to substantiate theoretical and methodic approaches to comprehension of the role and importance of the strategy of customer service of an industrial enterprise in terms of achievement of its sustainable competitive advantages. The article is devoted to the study and actualization of the strategy of customer service of an industrial enterprise in the context of implementation of the strategic management concept. Solution of the tasks, outlined in the article, is secured by general scientific and specific methods of research, i.e. analysis and synthesis, systematization and generalization. The work has actualized the strategy of customer service of an industrial enterprise in the contexts of implementation of the strategic management concept. The research identifies barriers on the way of the market entry, which are set by producers with a high level of customer service. The main barriers include the used schemes of payment, imposing heavy dependence between a customer and a supplier, as well as arrangement of a broad chain of servicing establishments, which are located at the places of customers’ employment, completion of contracts on continuous supply services, creation of the image of competence concerning services supply. The article examines the features, characterizing customer service of high quality, and identifies relationship between the strategy of competitive advantages of an enterprise and the strategy of customer service. The article supplies argumentation that servicing has become an accelerator of partnership relations setting between a customer and a supplier, as well as of achievement of a high level of customers’ loyalty. Shaping of the policy of customer service is an important direction to reach a competitive advantage of an industrial enterprise. The work proposes measures to motivate employees to supply customer service of the appropriate quality, which will secure establishment and support of the corporative culture, focused on the company’s clients. The principal scientific fundamentals of the article can be applied in the practical operation of industrial enterprises.